The pan-genome of Aspergillus fumigatus provides a high-resolution view of its population structure revealing high levels of lineage-specific diversity driven by recombination. - Lotus A Lofgren; Brandon S Ross; Robert A Cramer; Jason E Stajich (PLoS Biology, 2022)
Aspergillus fumigatus is a deadly agent of human fungal disease where virulence heterogeneity is thought to be at least partially structured by genetic variation between strains. While population genomic analyses based on reference genome alignments offer valuable insights into how gene variants are distributed across populations, these approaches fail to capture intraspecific variation in genes absent from the reference genome. Pan-genomic analyses based on de novo assemblies offer a promising alternative to reference-based genomics with the potential to address the full genetic repertoire of a species. Here, we evaluate 260 genome sequences of A. fumigatus including 62 newly sequenced strains, using a combination of population genomics, phylogenomics, and pan-genomics. Our results offer a high-resolution assessment of population structure and recombination frequency, phylogenetically structured gene presence-absence variation, evidence for metabolic specificity, and the distribution of putative antifungal resistance genes. Although A. fumigatus disperses primarily via asexual conidia, we identified extraordinarily high levels of recombination with the lowest linkage disequilibrium decay value reported for any fungal species to date. We provide evidence for 3 primary populations of A. fumigatus, with recombination occurring only rarely between populations and often within them. These 3 populations are structured by both gene variation and distinct patterns of gene presence-absence with unique suites of accessory genes present exclusively in each clade. Accessory genes displayed functional enrichment for nitrogen and carbohydrate metabolism suggesting that populations may be stratified by environmental niche specialization. Similarly, the distribution of antifungal resistance genes and resistance alleles were often structured by phylogeny. Altogether, the pan-genome of A. fumigatus represents one of the largest fungal pan-genomes reported to date including many genes unrepresented in the Af293 reference genome. These results highlight the inadequacy of relying on a single-reference genome-based approach for evaluating intraspecific variation and the power of combined genomic approaches to elucidate population structure, genetic diversity, and putative ecological drivers of clinically relevant fungi.